2021
DOI: 10.1186/s12968-021-00760-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Wilson disease on myocardial tissue and function: a cardiovascular magnetic resonance study

Abstract: Background Systemic effects of altered serum copper processing in Wilson Disease (WD) might induce myocardial copper deposition and consequently myocardial dysfunction and structural remodeling. This study sought to investigate the prevalence, manifestation and predictors of myocardial tissue abnormalities in WD patients. Methods We prospectively enrolled WD patients and an age-matched group of healthy individuals. We applied cardiovascular magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 64 publications
(102 reference statements)
4
10
1
Order By: Relevance
“…A study from Poland showed that heart involvement in WD was manifested mainly by mild morphologic and functional changes and was more positive in WD patients with neurological form [20]. As for the study from Germany, in which the ratio of patients with neurological presentation to those with nonneurological presentation reached to 33:43, ECG abnormalities were present in 45% of WD patients [9]. Compared with the German study, the incidence of ECG abnormalities in our study was lower (29.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from Poland showed that heart involvement in WD was manifested mainly by mild morphologic and functional changes and was more positive in WD patients with neurological form [20]. As for the study from Germany, in which the ratio of patients with neurological presentation to those with nonneurological presentation reached to 33:43, ECG abnormalities were present in 45% of WD patients [9]. Compared with the German study, the incidence of ECG abnormalities in our study was lower (29.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Based on some studies, ECG abnormalities are frequent in WD patients, which can occur at an early age [17,18]. Cardiac manifestations such as arrhythmias, autonomic dysfunction, cardiomyopathy and sudden cardiac death have been reported [9,16,19]. A study from Poland showed that heart involvement in WD was manifested mainly by mild morphologic and functional changes and was more positive in WD patients with neurological form [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper overload mainly occurs in the liver and brain and causes a variety of liver damage and neurological symptoms. Patients can be divided into WD-neuro + (patients with at least one neurological symptom) and WDneuro − (patients with a primarily hepatic involvement) patients [5,6]. However, several studies have shown that copper deposition can also occur in the heart and lead to clinical symptoms of related cardiovascular disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…arrhythmias, atrial fibrillation, heart failure, etc.) [6][7][8][9][10][11][12][13]. Therefore, early detection of myocardial involvement is important even in asymptomatic WD patients.…”
Section: Introductionmentioning
confidence: 99%